Embedded Linux system design and development - Raghavan, P. (Pichai), 1973-; Lad, Amol; Neelakandan, Sriram (Boca Raton, FL : Auerbach Publications, 2006)
Contains an embedded Linux system development roadmap for systems architects and software programmers. Explaining the issues that arise out of the use of Linux in embedded systems, this book facilitates movement to embedded Linux from traditional real-time operating systems, and describes the system design model containing embedded Linux.
Introduction History of Embedded Linux Why Embedded Linux? Embedded Linux Versus Desktop Linux Frequently Asked QuestionsEmbedded Linux Distributions Porting Roadmap Getting StartedArchitecture of Embedded LinuxLinux Kernel ArchitectureUser Space Linux Start-Up SequenceGNU Cross-Platform Toolchain Board Support Package Inserting BSP in Kernel Build ProcedureThe Boot Loader InterfaceMemory MapInterrupt ManagementThe PCI SubsystemTimersUART Power ManagementEmbedded Storage Flash MapMTD-Memory Technology DeviceMTD Architecture Sample MTD Driver for NOR FlashThe Flash Mapping DriversMTD Block and Character DevicesMtdutils PackageEmbedded File Systems Optimizing Storage SpaceTuning Kernel MemoryEmbedded Drivers Linux Serial DriverEthernet Driver I2C Subsystem on Linux USB Gadgets Watchdog Timer Kernel ModulesPorting ApplicationsArchitectural ComparisonApplication Porting RoadmapProgramming with PthreadsOperating System Porting Layer (OSPL)Kernel API DriverReal-Time Linux Real-Time Operating System Linux and Real-TimeReal-Time Programming in LinuxHard Real-Time Linux Building and DebuggingBuilding KernelBuilding Applications Building Root File System Integrated Development EnvironmentDebugging Virtual Memory ProblemsKernel DebuggersProfiling Embedded GraphicsGraphics System Linux Desktop Graphics-The X Graphics SystemIntroduction to Display HardwareEmbedded Linux GraphicsEmbedded Linux Graphics Driver Windowing Environments, Toolkits, and ApplicationsConclusionuClinux Linux on MMU-Less SystemsProgram Load and ExecutionMemory ManagementFile / Memory Mapping-The Intricacies of mmap()in uClinux Process Creation Shared Libraries Porting Applications to uClinux XIP-eXecute In PlaceBuilding uClinux DistributionAPPENDICESA Booting Faster Techniques for Cutting Down Bootloader InitializationTuning Kernel for Decreased Boot-Up Time Tuning User Space for Decreased Boot-Up Time Measuring Boot-Up Time B GPL and Embedded LinuxUser-Space Applications KernelPoints to Remember Notes
Includes bibliographical references and index.
CSE
Karim International
Keywords: Linux; Operating systems (Computers); Embedded computer systems; Computer science